Agrobiodiversity: an introductory resource book for students - Baral, K.P.; Joshi, M.; Basnet, B.M.S.; Tamang, B.B.; Subedi, A.; Gyaw, S. (2005)
This book in Nepalese language has been published by Nepal in situ Team for the school children to be taught in Schools in Nepal. Basically this book contains: Introduction on unique geography and socio-cultural settings of Nepal and overall biodiversity of Nepal (here information were illustrated with figures, tables and class exercise for students); what is biodiversity and its types (Ecosystem, Species and genetic diversity) (Illustrated with several line drawings, figures and examples); major threats and Importance of biodiversity; Introduction on agro biodiversity and its types; introduction and concept of centre of origin of crop genetic resources (provided with map, tables, short introduction on N.I. Vavilov); importance of agro biodiversity illustrated with figures on benefit of mono and mixed agro-farming system (exercises were provided from the Begans site experiences); erosion in agro biodiversity ( example were provided with fact figures of lost in crop genetic resources in China and Nepal case on rice landraces from Bara site); strategies for agro biodiversity conservation (Ex-situ, in situ and On-farm); details illustration of ex-situ conservation; in situ conservation and On-farm conservation (Introduction and differences).